Teaching Concerns in Higher Education: Impact of Covid-19 in Pedagogy - Alam, Sohaib; Hameed, Ansa (Journal of Education Culture and Society, 2023)
Thesis. The present study aims to explore the impact of Covid-19 on higher education and identify the different problems faced by pedagogues around the globe. It compares the outcomes and comments from both established and developing countries to understand the change in pedagogical procedures.Concept. The desire for social isolation that was unheard of until the 20th and 21st centuries became a catchall word during the pandemic. For educational institutions, the governments’ emergency measures to switch from traditional classroom settings to virtual alternatives generated important opportunities and problematic obstacles.Results and conclusion. The study was conducted thorough research of Covid-19's broad effects on pedagogical practices in higher education, from the viewpoints of both instructors and learners. An analysis of diverse secondary materials was carried out and conclusions were derived accordingly. The findings show that the pandemic caused distinct problems for different populations depending on selected criteria that were explored and emphasised in the proposed study.Originality. The study has thoroughly analysed the ideas, challenges, of online educational pedagogy to identify the effectiveness and challenges. The main research contribution is the finding that asserts the promise of technology and the challenges that students encounter when learning through digital processes.